Feasibility, Acceptability, and Adherence of Nutritional Supplement Amongst Pregnant Women in Rural Ethiopia. (7th June 2021) - Eglovitch, Michelle; Workneh, Firehiwot; Shiferaw, Tigest; Shiferie, Fisseha; Amanuel, Hanna; Tadesse, Amare Worku; Worku, Alemayehu; Isanaka, Sheila; Berhane, Yemane; Lee, Anne CC
Abstract: Objectives: Providing balanced protein energy (BEP) supplementation to pregnant women in low-and-middle income countries has been shown to improve pregnancy outcomes. The objective of this study was to assess the feasibility, acceptability, and adherence of a proposed BEP product among pregnant women in rural Ethiopia prior to initiation of a clinical effectiveness study. Methods: This formative study was conducted from October-November 2018 among pregnant women in the rural Amhara region of Ethiopia, prior to the "Enhancing Nutrition and Antenatal Infection Treatment (ENAT)" study [ISRCTN15116516]. Questionnaires to assess acceptability of a micronutrient fortified corn soy blend (CSB) BEP supplement were administered using a 7-point Likert scale (0 = strongly disagree, to 7 = strongly agree) after 2 and 4 weeks of utilization. Acceptability domains included: color, taste, texture, odor, portion size, ease of use, and adult favorability. Women were also given weekly provisions of daily sachets of the supplement and monitored weekly for adherence over one month. Results: 39 women participated in the study and 33 completed the study at 4 weeks. Quantitative results demonstrated high acceptability (mean Likert score >6 of 7) for the following domains: color, odor and perceived adult favorability at mid and end point. Scores on acceptability and perception of the product remained generally stable through the duration of use. The average number of sachets consumed was 6.4 in week 1, 6.6 in week 2, 7 in week 3, and 6.9 in week 4. 43% of women consumed the portion in one sitting, whereas 57% of women split up the portion to consume throughout the day. The majority (66%) of women reported consuming the full daily serving. 26% of respondents reported sharing the supplement with family members. Conclusions: These findings show that most women in rural Amhara, Ethiopia, found the BEP supplement acceptable and had positive perceptions of the product. Sharing of the product and completion of the full daily serving were important considerations. Overall, the BEP supplement demonstrated good feasibility of implementation in our study population. Future studies should consider utilizing such strategies to understand factors that may affect uptake and adherence of nutritional supplements. Funding Sources: Bill & Melinda Gates Foundation.